Non-native persons and the status of the artist - Addae, Jennifer; Souvereyns, Greet; De Gryse, Pieter; Timmermans, Jan (Brussels: Kunstenloket, 2009)
"Authors: Jennifer Addae - Vluchtelingenwerk Vlaanderen, Greet Souvereyns - Kunstenloket ; Preface: Pieter De Gryse, Jan Timmermans"